Evaluating the Implementation of Marine and Fisheries Technopark in Tegal, Indonesia Using Project Cycle Management - Sabana, Ady; Gestsson, Helgi Kristinarson (International Review of Management and Marketing, 2017)
In 2015 the government of Indonesia planned the construction of 100 technology parks, spread over the whole of the country, of which 24 Marine and Fisheries Technology Parks (MFTP) were to be built in the period from 2015 - 2019. To establish a sustainable operation of the Tegal MFTP within four years the study evaluates the implementation of the MFTP in Tegal, Central Java Province, Indonesia, using a Project Cycle Management (PCM). The Tegal MFTP has been in operations since 2015. Comparing performance to targets over the first two years has called for improvements. In 2015 four incubator activities were started up at the MFTP. Unfortunately, all but one incubator was discontinued 2016. Based on PCM analysis suggestions to improve the operational sustainability of the MFTP are presented. The suggestions cover various aspects for improvement regarding the operations for the Tegal MFTP as well as for the new MFTPs, both for those starting operations now and those still in the planning. These aspects are a financial support approach, a MFTP administrational approach, an innovative technology approach, and an incubator services approach seeking to improve the satisfaction of the participants/tenants. Keywords: Marine and fisheries Techno Park, Project cycle management, Business Incubator JEL Classifications: O22, O21